Rhizomic communication practices bridging international students and the host society and beyond - Jokila Suvi; Mathies Charles (Springer, 2025)
Evidence suggests that the COVID-19 pandemic has significantly impacted international student communities while reflecting wider societal inequalities. This study in the Finnish context examined international students’ experiences of the published national crisis communication and media usage during the first year of the pandemic. Using the national COVID-19 crisis communication practices as an example, we examined what kinds of strategies the international students deployed to access information in this non-English-speaking country and how they perceived the information communicated. Theoretically, we based the analysis on the theories of crisis communication and information inequality, which identify communication practices, such as language choice, that differentiate groups of people and impact their health outcomes. These are combined with rhizomic understanding, as reported by Deleuze and Guattari (1988/2020), of accessing media, and extended it to a mobile group of people (international students) living transnational lives. The data included interviews with international students studying at Finnish universities. The findings show that the students deployed five interlinked strategies to access information during the COVID-19 pandemic that highlight the heterogeneity of information and its usage, global asynchronousness of pandemic paths, and temporal changes in approaching information.